ANIMAL WELFARE: A STRATEGIC INVESTMENT FOR SUSTAINABLE MODERN FARMING - Agustina, Kadek Karang; Sukada, I Made; Kertawirawan, I Putu Agus; Segantara, Luh Gede Victoria; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2026)
Animal welfare has emerged as a fundamental pillar in the transformation of modern sustainable livestock farming. This study analyses the position of animal welfare as a strategic investment for enhancing product quality and optimizing operational efficiency in animal production. Through a systematic literature review of recent scientific publications, this research reveals that the implementation of animal welfare principles significantly reduces the incidence of PSE and DFD meat, decreases dependence on antibiotics, and improves both product quality and market competitiveness. Furthermore, animal welfare certification demonstrates proven efficacy in creating product added value and facilitating access to global markets. The study concludes that the integration of animal welfare represents an essential strategy toward sustainable livestock production. Therefore, integrated policies supporting animal welfare implementation through incentive schemes and certification program reinforcement are recommended.